Research on the Epic of Edigey in Türkiye - Kemaloğlu İ. (Золотоордынское обозрение)
Objective: The aim of the research is to reveal the history of studies in Turkey on the Edigey Epic, one of the most important epics in the Turkish world, to introduce the published copies of the Edigey Epic, and to determine from which perspectives the epic was researched and what kind of conclusions were reached. Research materials: The source of the study consists of copies of the epic published in Turkey, master’s and doctoral theses on the epic, and articles published in various scientific journals in Turkey on the subject. Results and novelty of the research: As a result of the research, it was determined that the Tatar, Bashkir, Nogay, and Kazakh versions of the epic were published in Turkey, two master’s and two doctoral theses were written on the Edigey Epic, and dozens of articles were written. Although the different versions of the Edigey Epic published in Turkey are attributed to different nations, in fact the subjects and heroes of all these publications are the same, and we see the differences only in the motives and cultural characteristics specific to these respective nations. As in many other fields, Tatar intellectuals were the first to research the epic in Turkey. On the other hand, articles written about the epic examine it in terms of history, literature, and language. These studies mostly attempt to reveal how the epic deals with the image of Edigey and Timur, the theme of homeland, weapons, steppe and steppe culture, birth-wedding-death, etc. In addition, some articles examine topics such as supernatural powers, mythological motives, and the functions of animals in the epic.